Trinitarian theology : theological models and doctrinal application - Ware, Bruce A., 1953-; Yarnell, Malcolm B., III.; Emerson, Matthew Y.; Stamps, Luke; Whitfield, Keith S. (Nashville, Tennessee : B&H Academic, 2018)
In recent years, debates over Trinitarian doctrine have emerged within evangelicalism. In Trinitarian Theology, contributors Bruce Ware, Malcon B. Yarnell III, Matthew Y. Emerson, and Luke Stamps discuss theological methods for forming the doctrine of the Trinity, and the the implications in applying that doctrine to complementarianism. Is this discussion important? The subject matter of Trinitarian Theology casts a long shadow over our faith. The Trinity is central to Christianity, for the vibrancy of our churches, and for the clarity of our witness in the world. The heart of Christianity is trinitarian, because central to the salvation story is the relationship between the Father and the Son. In short, this discussion is of great importance.
Unity and distinction of the Trinitarian persons / Bruce A. Ware -- From God to humanity : a Trinitarian method for theological anthropology / Malcolm B. Yarnell, III -- On Trinitarian theological method / Matthew Y. Emerson, Luke Stamps -- Response to Malcolm B. Yarnell III, Matthew Y. Emerson, and Luke Stamps / Bruce A. Ware -- Response to Bruce A. Ware, Matthew Y. Emerson, and Luke Stamps / Malcolm B. Yarnell, III -- Response to Bruce A. Ware and Malcolm B. Yarnell III / Matthew Y. Emerson, Luke Stamps -- Conclusion / Keith S. Whitfiled.
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed October 18, 2018).
Master record variable field(s) change: 050
Keywords: Trinity; God; Theology, Doctrinal; RELIGION / Christian Theology / General; God; Theology, Doctrinal; Trinity; Electronic books